2016
DOI: 10.1002/dc.23611
|View full text |Cite
|
Sign up to set email alerts
|

Using Computerized Cytomorphometry to Distinguish between Benign and Malignant Cases in Thyroid Fine‐Needle Aspiration Cytology

Abstract: Computerized cytomorphometry is useful in distinguishing between benign and malignant lesions in thyroid FNAC. The measurement of cytologic nuclear parameters in cases suggestive of AUS may be useful for the probable classification of cases as benign or malignant. Although further studies are needed, in nuclear morphometric assessment of thyroid FNAC, Giemsa staining may be more useful and valuable than the Pap stain because of its association with various cytologic nuclear parameters. Diagn. Cytopathol. 2016;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 18 publications
(79 reference statements)
0
12
0
Order By: Relevance
“…However, nearly all studies have used nuclear area as one of their indicators, and several have used some sort of measure of roundness/ovalness. In general, virtually all studies have found statistically significant differences in nuclear area (and many other nuclear features evaluated) between benign and PTC nuclei (Table ) . Many have reported sufficient overlap to limit the utility in clinical practice, but others have found that nuclear area, alone or in combination with other morphometric features, can achieve accuracy of 70% or greater .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, nearly all studies have used nuclear area as one of their indicators, and several have used some sort of measure of roundness/ovalness. In general, virtually all studies have found statistically significant differences in nuclear area (and many other nuclear features evaluated) between benign and PTC nuclei (Table ) . Many have reported sufficient overlap to limit the utility in clinical practice, but others have found that nuclear area, alone or in combination with other morphometric features, can achieve accuracy of 70% or greater .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, only some studies used air‐dried smears; air drying is likely to accentuate the variation in nuclear size/shape, and as such may be a better preparation for this purpose. However, 2 studies that evaluated both air‐dried Giemsa stains and alcohol‐fixed Papanicolaou‐stained smears found relatively similar effectiveness for both . Finally, many studies grouped cases of PTC, follicular carcinoma, and in some cases other carcinomas into a heterogeneous “malignant” group, which potentially enhances overlap between categories in a way that does not necessarily represent the pathologist’s differential diagnosis in individual cases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations